"I Haven't Got the Combination Yet!": The Embodied and Emotional Experiences of Dancers with Dyslexia and Other Invisible Disabilities. Issue 3 (3rd July 2022) - James, Tobin
ABSTRACT: Forms of disability that are not noticeably embodied, known as invisible disabilities (ID), are a source of stress and stigma for individuals with such diagnoses. For dancers with dyslexia or other ID, the decision to disclose to a dance teacher, director, or choreographer can either reduce pressure for the dancer or create an adverse presumption of incapability. This article contains the stories of six dancers (four female and two male), from a Midwestern metropolitan city, representing Black, Latinx, and White racial demographics. The experiences shared by the dancers with ID reflect how they are perceived and treated in and out of the studio. They also reveal the importance of understanding dancers with ID and the numerous challenges they face while working hard to learn and function within this demanding field.